Self-management challenges of adults with type 2 diabetes mellitus in Ekurhuleni district primary health care facilities amid COVID-19 lockdown - Siphiwe S. Mahlare; Melitah M. Rasweswe; Thifhelimbilu I. Ramavhoy (AOSIS, 2024)
Background: Self-management is highly recommended in managing type 2 diabetes mellitus (T2DM). Amid the coronavirus disease 2019 (COVID-19) lockdown, many restrictions were imposed, which might have affected the continuum of care and self-management. However, little is known about how people with T2DM experienced self-management during COVID-19 lockdown within the primary health care (PHC) facilities. Aim: The study explored and described the self-management challenges of adults with T2DM in Ekurhuleni PHC facilities amid COVID-19 level 5 and 4 lockdowns. Setting: The study was conducted in three community health centres in Ekurhuleni which are rendering PHC services. Methods: A phenomenological, qualitative, exploratory, and descriptive design was utilised. Purposive sampling was used to select adult patients with T2DM. Data were collected telephonically between July 2022 and August 2022 using semi-structured interviews. Inductive content analysis was used to analyse data. Results: Two themes emerged from the interviews, namely, uncontrolled blood glucose levels and financial challenges. Conclusion: The patients with T2DM experienced uncontrolled blood glucose levels and financial challenges during the COVID-19 lockdown. Guidelines to improve self-management programmes during restrictions are needed to promote good health during future pandemics to prevent complications and mortality. The telehealth model can be designed to monitor chronic patients at home during lockdown as a two-way communication. Contribution: More knowledge and insight into self-management and health promotion of patients with T2DM was provided by this study. Increased training needs arose for PHC nurses in managing and monitoring patients.